A New Disaggregated Set of Labor Market Indicators Using Standardized Household Surveys from Around the World - Montenegro, Claudio E. (Washington, DC: World Bank, 2012)
This paper presents a new database of disaggregated labor market indicators derived from a large set of surveys from developing countries. Four subsets of variables are included: (i) demographic, (ii) education, (iii) labor force, and (iv) welfare. A brief analysis of a subset of the labor market indicators is presented to illustrate the potential use of the database. The analysis highlights the very different structure of labor markets across developing regions and in particular, the unique characteristics of Sub-Saharan Africa, Eastern Europe, and Central Asia.